(untitled) (Acta Scientiarum. Technology, 2025)
Kombucha is a fermented beverage with an acid flavor, prepared from sweetened Camellia sinensis tea and a symbiotic culture of bacteria and yeasts, which are responsible for promoting the fermentative transformation. The Brazilian legislation allows the addition of several ingredients and considering the local biome, the objective of this work was to develop, characterize and evaluate kombuchas of green tea with the addition of Cerrado’s fruits: seriguela and guavira. The kombuchas of green tea, seriguela and guavira were fermented for 14 days, characterized and subjected to microbiological analysis, determination of phenolic compounds and antioxidant activity by ABTS and DPPH methods. The microbiological, pH and alcohol content standards required by the legislation were achieved. The highest content of phenolic compounds was found in the kombucha of green tea, followed by kombucha of guavira and kombucha of seriguela. The kombucha of guavira showed the highest antioxidant capacity, followed by the kombucha of green tea and the kombucha of seriguela, in both methods. The results demonstrate the potential production of bioactive compounds in kombuchas added to Cerrado’s fruits.